Upaya Meningkatkan Kemampuan Berhitung Anak Tunagrahita Ringan Menggunakan Media Kartu Angka 1-20 di SLB Negeri Manekat Niki-Niki - Dayu, Maria Yunistati; Selan, Ot Bil Wilson; Wangge, Vinsensius (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Children with mild intellectual disabilities, with an intelligence level of around 50–70, require a more concrete learning approach in order to master basic skills, including counting abilities. Difficulty in understanding numbers 1–20 often becomes an obstacle in their cognitive development and academic readiness. This study aims to improve the counting skills of children with mild intellectual disabilities through the application of number card media at SLB Negeri Manekat Niki-niki. The method used is classroom action research, involving four students who experience difficulties in basic mathematics. Interventions are conducted through structured learning activities that include the introductory, core, and closing stages. Data collection techniques are carried out through observation and tests. All research data are analyzed descriptively to determine the improvement in students' achievement results. The research results show that number card media are effective in improving the ability to recognize numbers, understand number concepts, and perform simple arithmetic operations. These findings confirm that concrete-visual media can be an alternative learning strategy relevant for children with mild intellectual disabilities, while also providing practical implications for special education teachers.